2014
DOI: 10.12691/ajphr-2-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Non-Communicable Diseases among Higher Secondary School Students in Selected Districts of India

Abstract: Background: Tobacco and harmful use of alcohol are two commonest modifiable risk factors leading to Non Communicable Disease. Tobacco and alcohol use during adolescence have potential long term health consequences and a possibility of future addiction. The present study aims to determine the prevalence of tobacco and alcohol use among school children in selected districts of India. Methods: A cross-sectional study was conducted among 4339 students (boys: 2587; girls: 1752) of 10-19 year sage group. Data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 6 publications
2
15
0
Order By: Relevance
“…Similar association was found in Indian studies and studies done in other countries. [7][8][9][10][11][12] Use of tobacco among family members was found to be a strong predictor for tobacco use among students with an odds ratio of 8 in the present study. A study from Sweden done to determine predictors of any tobacco use among adolescents showed an odds ratio of 1.15 for father currently smoking, odds ratio of 2.29 for mother currently smoking and an odds ratio of 3.03 for any other family member currently smoking.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Similar association was found in Indian studies and studies done in other countries. [7][8][9][10][11][12] Use of tobacco among family members was found to be a strong predictor for tobacco use among students with an odds ratio of 8 in the present study. A study from Sweden done to determine predictors of any tobacco use among adolescents showed an odds ratio of 1.15 for father currently smoking, odds ratio of 2.29 for mother currently smoking and an odds ratio of 3.03 for any other family member currently smoking.…”
Section: Discussionmentioning
confidence: 68%
“…6 The boys were more prone to ever/current use of tobacco as observed in other Indian studies. [7][8][9] The increased risk taking behavior among boys may be attributable to the greater freedom given to boys in Indian society and the influence of other male role models in their lives.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations